THE ADORABLE ADORO–A CASE REPORT - Maiti, Niladri; Das, Utpal Kumar (European Scientific Journal, ESJ, 2014)
Veneer restorations are well suited for conservative and aesthetic improvement of the anterior dentition.Indirect composite resin veneers present optimal aesthetics and durability.Indirect composite resin veneers utilize the advantages of both direct and indirect techniques in reconstruction of restorations with improved physical properties.The objective of this case report is to utilize the advantage of Indirect composite resin like ADORO in treating discoloured anterior tooth due to old restoration.